PATTERN OF BENZODIAZEPINE PRESCRIPTION IN INTERNAL MEDICINE OUTPATIENTS AT A TERTIARY CARE HOSPITAL IN PAKISTAN - Kazim, Mehrunissa; Abrar, Anam; Hanif, Madiha; Mansoor, Shafaq; Tahir, Sadaf; Mehmood, Asad; Yousafzai, Abdul Wahab (Journal of Postgraduate Medical Institute, 2015)
Objective: To explore the pattern of prescription of benzodiazepines in internal medicine outpatients at a tertiary care hospital. The study included thetypes of benzodiazepines used, gender and age preference, indication of prescription,past history of use, dosage and length of prescription. Methodology: This cross sectional study was undertaken from 1st of Januaryto1stof March 2011 at Internal medicine outpatients during this time were indentifiedthrough the hospital database. Relevant data from charts of patientswas recorded on a preformed questionnaire. All data collected was analyzedin SPSS 17.0. Results: Out of 1706 patients attending the outpatient clinics, 11.1% patientswere prescribed benzodiazepines. Female gender and older age was associatedwith higher rate of prescription. Intermediate acting benzodiazepines prescribed to 98.4% patients, were the most commonly prescribed drugs. Most common indication for prescription of benzodiazepine was anxiety anddepression. The length of prescription was mentioned in only 19% of cases. Only 24.3% patients had previously been prescribed the drug. Conclusion: The pattern of benzodiazepine prescription in tertiary care hospitalis comparable to that of developed countries. Due to the grave potentialfor abuse, regulation regarding the use of this class of drugs is extremelyimportant. Data from this study and other studies from the country seem tosuggest that awareness on this topic is in place. However, further widespreadstudies need to be carried out at the community level.